Behavioural responses of workers towards worker-produced male larvae and queen-produced worker larvae in Acromyrmex subterraneus brunneus Forel, 1911 (Hym., Formicidae) - Camargo, R. S.; Lopes, JFS; Forti, Luiz Carlos [UNESP] (Blackwell Publishing, 2006)
Leaf-cutting ant workers care for larvae with an elaborate behavioural repertoire to satisfy the needs of the offspring. In order to investigate worker discrimination ability in the leaf-cutting ant Acromyrmex subterraneus brunneus, we compared the behavioural responses of workers towards worker-produced male larvae and queen-produced worker larvae, including the following behavioural acts: licking the larval body, transporting larvae, feeding larvae with hyphae, scraping larval mouth parts, ingesting faecal fluid excreted by the larva, and inserting hyphae of the symbiontic fungus on the larval body. We verified that workers behaved differently depending on larval origin, i.e. licking the larval body, transporting larvae and inserting hyphae of the symbiontic fungus on the larval body. Observed differences denote the ability of workers in discriminating among larvae, probably because of their different individual needs.
Keywords: Acromyrmex subterraneus brunneus; leaf-cutting ant; worker reproduction